2005
DOI: 10.1128/aem.71.9.5129-5137.2005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Microbial Diversity and Seasonality in the Mexico City Metropolitan Area Water Supply System

Abstract: In the Mexico City metropolitan area (MCMA), 70% of the water for 18 million inhabitants is derived from the Basin of Mexico regional aquifer. To provide an overview of the quality of the groundwater, a longitudinal study was conducted, in which 30 sites were randomly selected from 1,575 registered extraction wells. Samples were taken before and after chlorine disinfection during both the rainy and dry seasons (2000-2001). Microbiological parameters (total coliforms, fecal coliforms, streptococci, and Vibrio s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
4
16
1
2
Order By: Relevance
“…Uncontrollable events, such as seasonal fluctuations of precipitation, can lead to even greater complexity. For example, a study of Mexico City's chlorinated DS found that levels of fecal streptococci were significantly higher in the dry season than in the wet season, whereas H. pylori levels remained fairly constant through the seasons [54]. This illustrates that uncontrollable complexity such as seasonal precipitation can lead to species-specific responses.…”
Section: Complexities Associated With Controlling Microbial Growthmentioning
confidence: 96%
“…Uncontrollable events, such as seasonal fluctuations of precipitation, can lead to even greater complexity. For example, a study of Mexico City's chlorinated DS found that levels of fecal streptococci were significantly higher in the dry season than in the wet season, whereas H. pylori levels remained fairly constant through the seasons [54]. This illustrates that uncontrollable complexity such as seasonal precipitation can lead to species-specific responses.…”
Section: Complexities Associated With Controlling Microbial Growthmentioning
confidence: 96%
“…Furthermore, these are studies that support the public's perception about the management and maintenance of the water distribution system, indicating that it is inadequate and insufficient, with 40% water loss due to leaks (Morales-Novelo and Rodríguez-Tapia 2007;Perló and González 2005) or significant fluctuations of the water quality (Mazari-Hiriart et al 2005). It should be noted that the research does not focus on poor management of the provider and is mainly based on the public's perception about water quality and supply, not taking into account the consumer's failure to properly maintain in-home water deposits such as pipes, faucets, roof tanks and underground cisterns.…”
Section: Introductionmentioning
confidence: 99%
“…70% of the water demand for a densely populated area with ca. 20 million inhabitants [15]. The third aquatic system was composed of a complex canal network (189 km) located in Xochimilco, south of the MCMA.…”
Section: Field Methodsmentioning
confidence: 99%